AGENTE DE SOFTWARE Q Y EL APRENDIZAJE DE MODELOS CONCEPTUALES - Maldonado Granados, Luis Facundo; Ortega del Castillo, Nerey; Ibáñez Ibáñez, Jaime; Sanabria Rodríguez, Luis Bayardo; Quintero Suárez, Victor Julio (Tecné, Episteme y Didaxis: TED, 2003)
We submit results of a research project focused on the relationship between a card arrangement exercise and the learning of conceptual models, built based on hierarchical ontologies. This approach is more frequent in measurement of attitudes - hot cognition, as it is expressed by Brown (1987) - or in opinion or subjectivity studies (Brown, 1980), and it is known as Q Methodology. A software agent - Q Agent - was programmed to be used either in a hypertext environment or as a companion to study press document and it’s effects on learning are explored. Two main comparisons are conducted: between use and non use of Q Agent, and between Q Agent with hypertext and Q Agent with pressed documents. The predictive value of student scores with the Q Agent in relation with student scores on a cognitive competence test is assessed as well. Three trials were carried on with a ninth grade student sample. Data are analyzed by means of ANOVA and multiple regression models. Significant effects of using the Q Agent were found, and scores on the Q Agent Game are significant predictors of scores on the cognitive competence test. Learning performance using Q Agent in hypertext environments drift lightly to be superior in relation to Q Agent with pressed documents. Results are discussed in the framework of information controlled autonomous learning systems, and the meaningful learning.